Struktura godichnogo sorevnovatel'no-trenirovochnogo tsikla podgotovki: Real'nost' i illyuzii - Suslov, F. P.; Shepel, S. P. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The article is dedicated to the analysis of the new tendencies of elite athletes' training at a year's competitive-training cycle in connection with the contemporary system of international sports competitions. The authors consider the problem of the sports form and training cycles' structure of elite athletes basing on the elaborations of L.P. Matveyev and A.P. Bondarchuk and the experts analyses' data. They conclude that the traditional (classic) structures of a years training cycles are uses by the contemporary elite athletes which use new training methods and ergogenic support at the same time.